Effect Of KCL Fertilizer Doses on Growth and Yield of Tomato (Lycopersicum Esculentum, Mill) Plant in Polybags - Nora Augustien (SEAN Institute, 2024)
Tomato plants (Lycopersicum esculentum, Mill) are fruit vegetable plants that people need every day. Procurement of tomatoes can be cultivated in polybag containers, planted in the yard or on the moor. The ability of tomato plants to grow in polybag containers requires nutritional support in the right dose, right type and at the right time so that production is optimal. One factor that needs to be considered is the vegetative growth process and preventing flower loss. The dry season greatly affects the plant growth process. By administering a dose of KCl to tomato plants, it is hoped that it will increase growth and prevent flower loss, making the process of flowers becoming fruit more optimal. The research was structured in a Randomized Block Design (RAK) consisting of 7 levels, namely D1=6 gr/plant, D2=7 gr/plant, D3= 8gr/plant, D4= 9gr/plant, D5=10gr/plant, D6=11gr/plant, D7= 12gr/plant, each treatment was repeated 3 times. The parameters that are considered are plant height, number of leaves, age at flower emergence, number of flowers, total number of fruit and fruit weight (g/plant). The results of the research showed that treatment with various doses of KCl fertilizer had no effect on the growth of plant height and number of leaves. A dose of 10 g/plant gave an increase of 0.89% in the age at which flowers appeared and an increase of 3.33% in the number of flowers compared to the recommended dose of 9 g/plant.